2023
DOI: 10.3390/life13030655
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fermentation on the Nutritional Quality of the Selected Vegetables and Legumes and Their Health Effects

Abstract: Vegetables are rich in many vitamins, mineral components, antioxidants, and macronutrients. However, they also contain high levels of anti-nutrients, which reduce the bioavailability of some nutritionally essential components such as zinc or iron. The processing of vegetables, including microbial fermentation, reduces or neutralizes tannins and phytates, which results in greater bioavailability of vitamins and minerals. Another effect of bacterial processing is an increased antioxidant potential, which has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 150 publications
0
15
0
Order By: Relevance
“…that the period with a decrease in temperature (reduced fermenters activities depreciate), the total phenols content remains on the rise suggesting that a prolonged fermentation period may favour an increase in phenolics compared to other phytochemicals estimated in this study. Knez et al [ 50 ] stated that ascorbic acid content in fermented samples is inversely proportional to the fermentation time in some selected vegetables and legumes.…”
Section: Discussionmentioning
confidence: 99%
“…that the period with a decrease in temperature (reduced fermenters activities depreciate), the total phenols content remains on the rise suggesting that a prolonged fermentation period may favour an increase in phenolics compared to other phytochemicals estimated in this study. Knez et al [ 50 ] stated that ascorbic acid content in fermented samples is inversely proportional to the fermentation time in some selected vegetables and legumes.…”
Section: Discussionmentioning
confidence: 99%
“…The overall increase of calcium, zinc, iron and potassium content as fermentation progressed could be attributed to enzymatic activity during fermentation, leading to mineral release and solubilization. For example, the rise of potassium content over fermentation days is linked to the enzymatic degradation of cellular components and the subsequent release of intracellular potassium (Knez et al , 2023). Ultimately, the mineral elements whose concentration increased exhibited strong adsorption to the dough matrix (Tee et al , 2023).…”
Section: Discussionmentioning
confidence: 99%
“…29 The inner mechanisms may be attributed to the probiotics and antioxidant potential in fermented vegetables. 41 Multiple lines of evidence indicate that dietary probiotics can restore the normal gut microbiome composition, and prevent and alleviate metabolic diseases by enhancing intestinal barrier integrity, reducing gut inflammation, and maintaining insulin sensitivity. [42][43][44] Experimental evidence has shown that Lactobacillus could alleviate hyperuricemia in rats, suggesting its potential therapeutic effect on patients with chronic hyperuricemia.…”
Section: Papermentioning
confidence: 99%